The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2309499019891208
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy-assisted surgery: The management of posterolateral tibial plateau depression fracture accompanying ligament injury: A case series and review of the literature

Abstract: Tibial plateau fractures are multiple fracture patterns associated with soft-tissue injuries. Among which, the combined existence of posterolateral tibial plateau depression fracture with anterior cruciate ligament (ACL) rupture has been reported rarely. Meanwhile, surgical method for the treatment of depression fracture is fairly complex. The aim of this article is to show a case series of this unusual injury pattern and the therapy of posterolateral tibial plateau depression fracture accompanying ACL rupture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Impression fractures of the PLTP, characterized by impression of the articular surface and impaction of the cortical bone of the tibial plateau, are among the wide variety of concomitant osteochondral lesions caused by the pivot‐shift injury mechanism, one of the most intense injury types [3–6, 28, 33]. Nevertheless, in recent decades, studies investigating concomitant osteochondral injuries have focussed mostly on bone bruises, and very little attention has been given to impaction fractures of the tibial plateau [3–6, 19, 25, 28, 37, 39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impression fractures of the PLTP, characterized by impression of the articular surface and impaction of the cortical bone of the tibial plateau, are among the wide variety of concomitant osteochondral lesions caused by the pivot‐shift injury mechanism, one of the most intense injury types [3–6, 28, 33]. Nevertheless, in recent decades, studies investigating concomitant osteochondral injuries have focussed mostly on bone bruises, and very little attention has been given to impaction fractures of the tibial plateau [3–6, 19, 25, 28, 37, 39].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no studies in the current literature investigating the biomechanical influence of these fractures on the kinematics of ACL‐deficient joints. However, several biomechanical studies have already shown the important role of the posterior horn and roots of the LM on knee kinematics, especially in terms of anterior tibial translational (ATT) and anterolateral rotational (ALR) stability [14, 24, 34, 37]. It has been reported that the posterior horn of the lateral meniscus (PHLM) acts as a wedge to stop the LFC during ATT and internal rotation (IR) of the tibia [14, 17, 24, 34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tibial platform fractures are an internal knee fracture, and open reduction internal fixation surgery can restore joint consistency, axial alignment, and joint stability (27), and can be practical while reducing the risk of post-traumatic arthritis early limb activity. Current surgical treatments for tibial platform fractures are internal fixation of internal and lateral locking plate, cortical bone screw and intramedullary nail, and external fixation (28). The surgical mode and rehabilitation concept are also being gradually improved (29).…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al reported two cases with combined ACL rupture and isolated posterolateral tibial plateau fracture and hypothesized the potential injury mechanism follows: the ACL initially ruptured under the force leading to violent internal tibial rotation/anterior tibial translation, followed by the posterolateral tibial plateau fracture stroked by the femoral condyle when the knee was subluxated and internal tibial rotated [ 11 ]. Wang et al reported 3 cases of posterolateral tibial plateau depression fracture associated with rupture of the ACL and MCL, and considered the ACL and MCL injury as a result of the vigorous internal rotation of the tibial or anterior tibial shifting with the knees in a forced valgus mechanism [ 12 ]. It is deduced that, in our case, a similar mechanism may play a part, and followed by an eccentric quadriceps' contracture leading to the full tear of the patellar tendon.…”
Section: Discussionmentioning
confidence: 99%